Meta-analysis of venous anastomosis techniques in free flap reconstruction - Geierlehner, A; Rodi, T; Mosahebi, A; Tanos, G; Wormald, J (Elsevier, 2019)
Background Coupler devices and hand-sewn anastomosis techniques are both routinely employed for venous anastomosis in microsurgical free flap transfer. However, uncertainty remains about whether those two techniques are different in terms of risk of venous thrombosis. The aim of this review was to evaluate the quality of the evidence and quantify the difference in venous thrombosis rates in both techniques.